2022
DOI: 10.3390/ijms23158578
|View full text |Cite
|
Sign up to set email alerts
|

VIP/VPAC Axis Expression in Immune-Mediated Inflammatory Disorders: Associated miRNA Signatures

Abstract: Few studies have considered immune-mediated inflammatory disorders (IMID) together, which is necessary to adequately understand them given they share common mechanisms. Our goal was to investigate the expression of vasoactive intestinal peptide (VIP) and its receptors VPAC1 and VPAC2 in selected IMID, analyze the effect of biological therapies on them, and identify miRNA signatures associated with their expression. Serum VIP levels and mRNA of VPAC and miRNA expression in peripheral blood mononuclear cells wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…One study examined the change of serum VIP level after treatment for immune mediated inflammatory diseases (including psoriasis and psoriatic arthritis) by biological agents and showed that TNF-α treatment can increase the level of serum VIP, while anti IL-12/23 treatment can reduce circulating VIP. 59 Another study found that narrowband ultraviolet B (NB-UVB) treatment had no significant effect on serum neuropeptide including SP, CGRP, brain-derived neurotrophic factor (BDNF), or corticotropin-releasing factor (CRF) levels. 64 As mentioned earlier, psoriasis symptoms can reappear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study examined the change of serum VIP level after treatment for immune mediated inflammatory diseases (including psoriasis and psoriatic arthritis) by biological agents and showed that TNF-α treatment can increase the level of serum VIP, while anti IL-12/23 treatment can reduce circulating VIP. 59 Another study found that narrowband ultraviolet B (NB-UVB) treatment had no significant effect on serum neuropeptide including SP, CGRP, brain-derived neurotrophic factor (BDNF), or corticotropin-releasing factor (CRF) levels. 64 As mentioned earlier, psoriasis symptoms can reappear.…”
Section: Discussionmentioning
confidence: 99%
“…A clinical experimental study observed that the plasma VIP level of the psoriasis group was significantly higher than that of the control group. 59 Immunohistochemical analysis showed that the number of VIP positive nerve fibers was significantly higher than that of psoriasis non lesional skin and healthy control skin. 4 VIP has different effects on DCs in various differentiation and stimulation states.…”
Section: Effect Of Neuropeptides On Dcsmentioning
confidence: 96%